Oral delivery system for tetanus toxoid - AHIRE, VJ; DOSHI, JB; RAVETKAR, SD; SAWANT, KK (Ars Pharmaceutica (Internet), 2007)
Systemic and local immune response against tetanus toxoid (TT) encapsulated in chitosan (CS) microparticles (CSTT)prepared by ionic cross-linking using Sodium Tripolyphosphate (STPP) was studied. CS-TT microparticles, TTin PBS and plain CS microparticles were orally administered to mice and TT (adsorbed) was administered throughintramuscular route. Sera were analyzed for anti-TT IgG and intestinal lavage for anti-TT IgA levels using an ELISA.The study shows the effi cacy of chitosan microparticle suspension system, containing a TT, in inducing the IgA inintestine and IgG in systemic circulation.